227k views
0 votes
If f(x)=3x^(2)+1 and G(x)=2x-3 what would f(f(x))

User Jacopofar
by
5.3k points

2 Answers

1 vote

Hello,


(fof)(x)=f(f(x))\\\\=3(3x^2+1)^2+1\\\\=3(9x^4+6x^2+1)+1\\\\\boxed{=27x^4+18x^2+4}

User Eiconic
by
5.8k points
1 vote

Answer:

f(f(x)) = 27
x^(4) + 18x² + 4

Explanation:

To find f(f(x)) substitute x = f(x) into f(x) , that is

f(3x² + 1)

= 3(3x² + 1)² + 1 ← expand parenthesis using FOIL

= 3(9
x^(4) + 6x² + 1) + 1 ← distribute parenthesis by 3

= 27
x^(4) + 18x² + 3 + 1 ← collect like terms

= 27
x^(4) + 18x² + 4

User Paul Cavacas
by
5.1k points